2011
DOI: 10.1007/s00776-011-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of shelf acetabuloplasty for developmental dysplasia of the hip in adults: a minimum 20-year follow-up study

Abstract: BackgroundShelf acetabuloplasty has been applied to secondary osteoarthritis of the hip due to congenital dislocation or acetabular dysplasia; however, there are few reports on the long-term outcomes of this operation. Here, we aimed to investigate the long-term effects of our shelf acetabuloplasty for developmental dysplasia of the hip in adults.MethodsOutcomes for 28 hips (7 with pre-arthrosis, 21 with initial stage of arthrosis) were retrospectively reviewed clinically and radiologically at a minimum of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 17 publications
(22 reference statements)
0
41
0
1
Order By: Relevance
“…Kaplan-Meier survival analysis with THA as endpoint ( Figure 2) was documented by 5 studies (Migaud et al 2004, Fawzy et al 2005, Berton et al 2010, Hirose et al 2011, Tanaka et al 2018. Fawzy et al (2005) analyzed 76 hips from 67 patients with an average age of 33.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan-Meier survival analysis with THA as endpoint ( Figure 2) was documented by 5 studies (Migaud et al 2004, Fawzy et al 2005, Berton et al 2010, Hirose et al 2011, Tanaka et al 2018. Fawzy et al (2005) analyzed 76 hips from 67 patients with an average age of 33.…”
Section: Resultsmentioning
confidence: 99%
“…Various types of periacetabular osteotomy have been performed for adolescents and adults with developmental dysplasia, and good longterm results have been reported [4][5][6][7][8][9]. There are 3 important requirements for the success of joint-preserving surgery [10]: creation of a larger articular surface, preservation of muscle strength, and creation of a favorable condition for THA at a later stage.…”
Section: Discussionmentioning
confidence: 96%
“…Various types of acetabular osteotomies have been performed to delay progression of osteoarthritis or treat early osteoarthritis in adolescents and young adults; furthermore, many satisfactory long-term results have been reported [4][5][6][7][8][9]. However, some patients must undergo conversion arthroplasty because of continued pain or progression of hip arthritis after osteotomy [7,10].…”
mentioning
confidence: 96%
“…The principle shelf procedure for DDH was originally described by Konig in 1891 [7] and seems to be a safer and simpler technique compared with periarticular acetabular osteotomies. Furthermore, several studies on the long-term results of shelf procedures have reported highly encouraging survival rates [8][9][10][11]. However, the most commonly used approach for the shelf procedure, the Smith-Peterson approach, exposes a large section of the iliac crest via a long skin incision and is relatively invasive.…”
Section: Introductionmentioning
confidence: 99%